Automatic Control Room Temperature - Muhammad Zubir, Omar (UTeM, 2010)
Technological developments affecting the system 'Microcontroller' allows people to control various activities and processes within the industry automatically. For this project, system Microcontroller is used to replace human labor in the regulation of temperature changes and notification of the status of a room as operating rooms machine etc. Conditions in a room can be identified when there is a sudden temperature increase or decrease due to operating a machine. Given this situation, a tool developed to control the status of the particular machine in the room whether it works properly or not through a temperature change in the room. Fan (fan eczos) operates automatically according to changes in room temperature. To detect changes in room temperature, a temperature sensor (type: LM35DZ) was used. This temperature sensor will send a signal to microcontroller (model: pic16f876a) and the microcontroller will determine the level of speed eczos fan either fast, medium and slow, and Strobe light on the signal received from the temperature sensor.